2021
DOI: 10.1002/cncr.33875
|View full text |Cite
|
Sign up to set email alerts
|

Risk of prostate cancer for men with prior negative biopsies undergoing magnetic resonance imaging compared with biopsy‐naive men: A prospective evaluation of the PLUM cohort

Abstract: BACKGROUND: Men with prior negative prostate biopsies have a lower risk of being diagnosed with prostate cancer in comparison with biopsy-naive men. However, the relative clinical utility of identified lesions on multiparametric magnetic resonance imaging (mpMRI) is uncertain between the 2 settings. METHODS: Patients from the Prospective Loyola University mpMRI (PLUM) Prostate Biopsy Cohort (January 2015 to June 2020) were examined. The detection of any prostate cancer and clinically significant prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…In this multi‐institutional study of men with a PI‐RADS 3 index lesion who underwent mpMRI‐targeted biopsy, CSPCa was detected in approximately 17% of men. This is consistent with the reported detection rates of approximately 20% 8, 9, 11, 13, 18 . Interestingly, targeted biopsy alone detected the highest GG of CSPCa in only 37.5% of men with a PI‐RADS 3 index lesion, whereas a template biopsy detected the highest GG in 42.1% of men.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this multi‐institutional study of men with a PI‐RADS 3 index lesion who underwent mpMRI‐targeted biopsy, CSPCa was detected in approximately 17% of men. This is consistent with the reported detection rates of approximately 20% 8, 9, 11, 13, 18 . Interestingly, targeted biopsy alone detected the highest GG of CSPCa in only 37.5% of men with a PI‐RADS 3 index lesion, whereas a template biopsy detected the highest GG in 42.1% of men.…”
Section: Discussionsupporting
confidence: 90%
“…The application of their model produced an AUC of 0.84, and biopsies were reduced by 18% without any CSPCas being missed. Patel et al 13 recently created their own risk model after analyzing 900 men who were either biopsy‐naive or had a prior negative biopsy. They too found that age, PSA density, prostate volume, and PI‐RADS score were predictive of CSPCa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the patients of this cohort were biopsy-naïve, and the biopsy setting could influence the performance of models. A prospective study involving 900 patients conducted by Patel et al illustrated that patients with prior negative biopsies had lower PCa detection (27.9% vs 54.4%) in comparison with biopsy-naive men (35), demonstrating the importance of the biopsy setting in cancer detection.…”
Section: Discussionmentioning
confidence: 99%